Access to Justice and the Reform of the Constitutional Protection Mechanism in Vietnam - Tuan, Dang Minh (VNU Journal of Science: Legal Studies; Vol 34 No 1DO - 10.25073/2588-1167/vnuls.4144, 2018)
Constitutional protection is a topic that has been discussed extensively in our country in recent years, but has not been studied in terms of access to justice. This article analyzes some of the general issues of the relationship between access to justice and constitutional protection, thereby assessing constraints, prospects and solutions for securing access to justice through constitutional protection mechanism in Vietnam. Keywords Access to justice, constitutional protection, judicial review, Vietnamese Constitution